Aplikasi Toko Buku Berbasis Web Dengan Fitur Rekomendasi Buku Menggunakan Algoritma Collaborative Filtering - Adhitya Ilham Ramdhani; Sabar Hanadwiputra; Subandri Subandri; Zaenal Mutaqin Subekti (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2026)
The rapid development of information technology has had a significant impact on various sectors, including the bookselling industry. Many conventional bookstores have begun to switch to digital platforms, simplifying and expanding their sales reach. However, with the wide selection of books available, users often experience difficulty finding books that match their interests and needs. Therefore, this research was conducted with the aim of designing a web-based bookstore application equipped with a personalized book recommendation feature using the PHP programming language and a MySQL Database. The main feature is the implementation of a collaborative filtering algorithm, a recommendation system method that analyzes the similarity of preferences between users based on data from ratings provided. This data is used to predict and recommend books that are likely to be liked by other users with similar preference patterns. The implementation of this algorithm aims to increase the relevance of recommendations and provide a more efficient and interactive book search experience. The results of this test indicate that the system is capable of providing relevant book suggestions that align with user preferences. Furthermore, the implementation of this web-based application also simplifies the transaction process, speeds up book searches, and increases user satisfaction in digital shopping. Thus, this web-based bookstore application that uses a collaborative filtering algorithm can be an effective solution in helping users find books according to their interests and supporting the development of digital bookstores.